Juicio moral de adolescentes de 14 y 16 años, universitarios y adultos de clase socio-económica media de Lima - Majluf, Alegría (1986)
Moral Judgement development was studied in 84 Lima middle-class subjects of different ages (range 14-60 years). The referential theory in this study was Kohlberg's and the instrument was the Multiple Choice Measure of Moral Reasoning- SROM developed by Gibbs ( 1984 ). The main purpose was to test the universality of the theory and the stages. Results seem to support the claim of universality and were sensibly the same that those reported by researchers in the USA. No differences between sexes wasfound